Consumer Response to Selfies in Advertisements: Visual Rhetoric for the Me Me Me Generation. Issue 2 (4th May 2019) - Holiday, Steven; Loof, Travis; Cummins, R. Glenn; McCord, Amber
Abstract: Marketers continually seek ways to capture the attention of an audience largely motivated to avoid advertising messages. The recent rise in the use of the selfie as a legitimate photographic genre and casual form of communication has afforded marketers a new avenue to catch the eye of potential consumers. By using an experimental research method that utilizes eye tracking, this study examined the unique composition of the selfie and identified that this form of photography enhances viewers' sense of interpersonal connection with the subjects of these images, and produces tangible outcomes that have practical implications for consumer behavior.